ASPEK-ASPEK PEMBELAJARAN SADAR WISATA KERIS MADURA UNTUK MENINGKATKAN KETERAMPILAN BERBAHASA DI KALANGAN SISWA DALAM MENDUKUNG WISATA HALAL - Fachrur Rozie; Fiyan Ilman Faqih; Prita Dellia; Ahmad Jami’ul Amil (BASA Journal of Language & Literature, 2022)
Halal tourism is one of Madura's potentials and is now continuing to be developed to find the main goal, namely increasing the welfare of the Madurese people. One of the components to achieve this goal is education. Therefore, this study aims to find out aspects of keris tourism awareness learning in the education sector, especially language so that it can become a new or more understanding among students. This research is a qualitative descriptive study. This study will describe the important aspects that are present in Indonesian language learning based on tourism awareness learning. In addition, this study also describes the aspects that cause problems in teaching teachers in schools related to basic travel learning. Therefore, there are two important things that result from this research, namely an explanation of the issues of culture-based learning and important aspects that must be present in tourism-conscious learning to support halal tourism conducted by teachers.